Thai AEC Engineer Readiness: A Confirmatory Factor Analysis - Kraisuth, Duangporn; Panjakajornsak, Vinai (My University, 2018)
At the start of 2016, the 10 nations of the Association of Southeast Asian Nations (ASEAN) entered a new era. With it, came the decade-old start of the implementation of the 2005 mutual recognition arrangement (MRA) on engineering services, and the free flow of skilled labor (FFSL). Although created with noble intentions, actual specifications and qualifications for an individual’s foreign employment heavily restricts its actual implementation. This study, therefore, conducted a confirmatory factor analysis using LISREL 9.1 software of 278 engineers selected from a population of 1,211 Thai Federation of Industries companies to investigate how need, gap, and competency affect readiness. From the analysis, need was shown to have the highest effect on readiness, whereas competency also had a direct effect on readiness. Finally, the research determined that less than 1% of the surveyed engineers were certified as ASEAN engineers, which is a precondition for registration for work as an engineer in another ASEAN country, and that cultural awareness of other member nations was perceived as the weakest link in an individual’s engineer readiness perception.
Keywords: ASEAN; competency; FFSL; gap; MRA; need